A Note on Spatial Price Discrimination - Singer, H. W. (Review of Economic Studies, 1937)
Journal Article A Note on Spatial Price Discrimination Get access H. W. Singer H. W. Singer London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 5, Issue 1, October 1937, Pages 75–77, https://doi.org/10.2307/2967583 Published: 01 October 1937